A Survey on Stress Detection using Data Mining Techniques - Yemunarane, K; Hema, A (International Journal of Computer Sciences and Engineering, 2025)
Stress is actually survival response when our body gets any outside force or event. The human body is designed to experience stress and react to it. Stress can be positive, keeping us alert, motivated and ready to avoid danger. Sometimes the stress becomes negative when a person faces continues challenges without any relaxation, mental tension caused by demanding, conflicts with others. Stress that continues without relief, a hormone called coristol is released into blood stream suppressing the functioning of immune, digestive and reproductive system. Because of this it is important to practice stress management in order to keep our body healthy. The purpose of this study is to find out the level of stress among various categories of people like school going students, working people and people under medical treatment using data mining techniques. Data mining is a process used in many areas to turn raw data into useful information. It is the process of discovering patterns in large data sets involving methods at the intersection of machine learning, statistics, and database systems